Implementasi Enterprise Resource Planning (ERP) Terhadap Perkembangan UMKM (Studi Kasus Mitra Motor Toyota) - Lucky Hartanto Salim; Lufty Abdillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The use of information technology is one of the important things in the business world, this is not only limited to using computers or other technological aids in the business world, but using software that has been provided to assist business owners' business processes. Mitra Motor Toyota is an MSME engaged in the automotive sector with a focus on spare parts for four-wheeled vehicles, the business owner said that the difficulty in calculating stock, especially during stock taking is due to not having a system and everything is still based on manual or self-calculated, then another thing is notes transactions that are often lost due to recording using makeshift paper. The implementation using the Zoho system in MSME businesses aims to solve the problems mentioned above, and of course the implementation uses the ERP Life Cycle method so that it can achieve maximum results.